Tax object data processing and taxpayer determination in improving pbb target achievements at Purwakarta - Ai Surtika Dewi; Eti Jumiati; Yanti Nuryani (Jurnal Mantik, 2024)
This research aims to analyze Tax Object Data Processing and Taxpayer Determination in Increasing the Achievement of PBB Targets at the Purwakarta Regency Bapenda. The data sources in this research were obtained from observations, interviews and documentation. The number of informants involved in this research was 4 people, they were the Head of Purwakarta Regency Bapenda, Head of Billing Division, Head of PBB-P2 Determination Agency, PBB Assessment Data and Information Manager and Collector. The research findings show that the processing of tax object data and determining taxpayers in Purwakarta Regency is quite good because it is proven that tax processing has an important role in managing taxation and increasing the achievement of PBB targets. And it is proven that this achievement from 2018 – 2023 continues to increase. Strategy for processing tax object data and determining taxpayers in increasing the achievement of PBB targets at the Purwakarta Regency Bapenda with steps such as direct service to the community through "pick up the ball" activities in sub-districts, socializing the use of tax payment applications as well as making PBB payments mobile via various platforms such as banks, the Siceupol application, PT POS Indonesia, Alfa Mart, Traveloka, Tokopedia, OVO, and Bukalapak, are very relevant to achieving PBB targets. The PBB fine elimination program was also carried out to increase tax payments and provide convenience to taxpayers. The evaluation carried out also helps in monitoring and improving tax target achievements.